1989
DOI: 10.1172/jci114190
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and cytoskeletal association of a major cell surface glycoprotein, GP 140, in human neutrophils.

Abstract: The binding of specific ligands to neutrophil cell surface receptors and the association of these receptors with the cytoskeleton may represent an essential step in activation. To identify surface proteins that are linked to the cytoskeleton during activation, neutrophil l25l-surface labeled plasma membranes were extracted with Triton X-100, and the soluble and insoluble (cytoskeleton) fractions analyzed by SDS-PAGE and autoradiography. The major cell surface proteins recruited to the cytoskeleton after activa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

1990
1990
2005
2005

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 63 publications
2
5
0
Order By: Relevance
“…Internalization is not clatharin dependent but does bind to cytoskeletal elements. This is consistent with WGA also binding to cytoskeletalanchored glycoproteins in various types of cells (Kalomiris and Bourguignon, 1988;Lehto and Virtanen, 1983;Mehta et al, 1999;Suchard and Boxer, 1989) and altering F-actin (Sjolander and Magnusson, 1988). Uptake is energy dependent and partially inhibited by potassium.…”
Section: Hiv-1supporting
confidence: 71%
“…Internalization is not clatharin dependent but does bind to cytoskeletal elements. This is consistent with WGA also binding to cytoskeletalanchored glycoproteins in various types of cells (Kalomiris and Bourguignon, 1988;Lehto and Virtanen, 1983;Mehta et al, 1999;Suchard and Boxer, 1989) and altering F-actin (Sjolander and Magnusson, 1988). Uptake is energy dependent and partially inhibited by potassium.…”
Section: Hiv-1supporting
confidence: 71%
“…Treatment with either trypsin or human leukocyte elastase has been shown to cleave CR1, but not CR3, on activated human PMN as measured by FACS scanning (20,32). In preliminary studies in our laboratory, we have found that elas- (36,37). Moreover, a subset of plasma membrane CR3 has recently been described that appears to be involved in phagocytosis of particles by several different receptors including CR1 and FcR.…”
Section: Discussionmentioning
confidence: 92%
“…However, crosslinking of cell surface receptors by antibody on B cells (Braun et al, 1982;Woda and McFadden, 1983;Woda and Woodin, 1984), T leukemic cells (Marano et al, 1989), and neutrophils (Jack et al, 1986), as well as lectin-induced receptor crosslinking on neutrophils (Suchard and Boxer, 1989) and PC12 pheochromocytoma cells (Vale and Shooter, 1982), does lead to receptor detergent-insolubility even if the assays are performed at 4°C. Although not measured in any of these cases, it is unlikely that any enzyme-based signaling mechanisms would be active at 40C.…”
Section: Discussionmentioning
confidence: 99%